2022
DOI: 10.1097/md.0000000000028130
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, pathological characteristics, and clinical management of black pleural effusion

Abstract: Background: Pleural effusion is characterized by excessive fluid collection in the pleural cavity. Black pleural effusion (BPE) is a rare entity with only limited scientific data. We aimed to review the current literature on black pleural effusion to characterize demographics, etiology, clinical presentation, pathological findings, available treatment strategies, and prognosis of this rare condition.Methods: We performed a systematic review of case reports and series and synthesized data on demographics, manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
(211 reference statements)
2
6
0
Order By: Relevance
“…Similarly, the maximum number of PE cases was seen in the age group of 55–65 and 65–75 years. This is in accordance with studies by Abramowitz et al 3 , Saha et al 24 , and Yousaf et al 25 , which also showed similar sex and age distribution.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the maximum number of PE cases was seen in the age group of 55–65 and 65–75 years. This is in accordance with studies by Abramowitz et al 3 , Saha et al 24 , and Yousaf et al 25 , which also showed similar sex and age distribution.…”
Section: Discussionsupporting
confidence: 93%
“…Treatment of black pleural effusion requires management of the underlying disease, such as chemotherapy for cancer or antifungal agents for fungal infections. [10] In the present case, steroid therapy for autoimmune pancreatitis resolved the pleural effusion without recurrence. Patients with autoimmune pancreatitis receive steroid therapy, which is effective in many cases.…”
Section: Discussionsupporting
confidence: 49%
“…To date, 9 cases of black pleural effusion caused by pancreaticopleural fistulae have been reported. [10] Of those, 8 cases were caused by alcoholic pancreatitis, while the remaining case was induced by idiopathic pancreatitis. [2][3][4][5][6][7][8][9]15] Almost all (99%) pancreaticopleural fistulae associated with a pancreatic pseudocyst are caused by alcoholic pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Black pleural effusions are extremely rare presentations and have been reported previously in only a handful of patients with lung malignancy, metastatic melanoma, pancreatic-pleural fistula, rupture of the pancreatic pseudocyst, biliopleural fistula, fungal infections of Aspergillus niger and Rhizopus oryzae [ 1 , 2 ]. Identifying the etiology of the pleural effusion and initiating appropriate management are crucial to preventing fatal complications such as respiratory failure and recurrent accumulation of pleural effusions.…”
Section: Introductionmentioning
confidence: 99%